2015
DOI: 10.2147/vhrm.s50368
|View full text |Cite
|
Sign up to set email alerts
|

Epoprostenol sodium for treatment of pulmonary arterial hypertension

Abstract: The release of endogenous prostacyclin (PGI2) is depressed in patients with pulmonary arterial hypertension (PAH). PGI2 replacement therapy by epoprostenol infusion is one of the best treatments available for PAH. Here, we provide an overview of the current clinical data for epoprostenol. Epoprostenol treatment improves symptoms, exercise capacity, and hemodynamics, and is the only treatment that has been shown to reduce mortality in patients with idiopathic PAH (IPAH) in randomized clinical trials. We have re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…Prostacyclin (also known as prostaglandin I 2 ) is produced in vascular endothelial cells and acts via the prostacyclin receptor (IP) of pulmonary artery smooth muscle cells (PASMCs) to cause vasodilation and inhibit PASMC proliferation (LeVarge, 2015 ). Prostacyclin production and IP expression are reduced in PAH (Saito et al, 2015 ), and analogs of prostacyclin are recommended as a pharmacotherapeutic option for patients with PAH in WHO Functional Class III/IV (Galie et al, 2016 ). The selective IP agonist oral selexipag has also displayed therapeutic effects, with acceptable tolerability in patients with PAH (Del Pozo et al, 2017 ; Honorato Pérez, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prostacyclin (also known as prostaglandin I 2 ) is produced in vascular endothelial cells and acts via the prostacyclin receptor (IP) of pulmonary artery smooth muscle cells (PASMCs) to cause vasodilation and inhibit PASMC proliferation (LeVarge, 2015 ). Prostacyclin production and IP expression are reduced in PAH (Saito et al, 2015 ), and analogs of prostacyclin are recommended as a pharmacotherapeutic option for patients with PAH in WHO Functional Class III/IV (Galie et al, 2016 ). The selective IP agonist oral selexipag has also displayed therapeutic effects, with acceptable tolerability in patients with PAH (Del Pozo et al, 2017 ; Honorato Pérez, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies often focused on the mechanism of changes in related bioactive molecules involved in regulating functions such as proliferation, apoptosis and migration (79). Results obtained from other studies revealed that anoxia can significantly downregulate the expression of PASMC contractile phenotype marker proteins (10,11). However, the specific mechanism of this downregulation is still unclear.…”
Section: Introductionmentioning
confidence: 82%
“…In the case of TRAIL and FasL, we have shown a noticeable increase in the gene expression for both targets during the hypoxic exposure of PASMCs, as compared to their respective normoxic controls. Limited evidences from the literature implicated these two signals in the context of pulmonary vascular disease (Hameed et al, 2012; Saito et al, 2015). Interestingly, although TRAIL is usually considered as pro-apoptotic mediator, its role in experimental PH pathogenesis has been described (Hameed et al, 2012).…”
Section: Discussionmentioning
confidence: 99%